Acute Myeloid Leukemia with Basophilic Differentiation Transformed from Myelodysplastic Syndrome - Yasuhiro Tanaka; Atsushi Tanaka; Akiko Hashimoto; Kumiko Hayashi; Isaku Shinzato (Case Reports in Hematology)
Myelodysplastic syndrome (MDS) terminally transforms to acute myeloid leukemia (AML) or bone marrow failure syndrome, but acute myeloid leukemia with basophilic differentiation has been rarely reported. An 81-year-old man was referred to our department for further examination of intermittent fever and normocytic anemia during immunosuppressive treatment. Chromosomal analysis showed additional abnormalities involving chromosome 7. He was diagnosed as having MDS. At the time of diagnosis, basophils had not proliferated in the bone marrow. However, his anemia and thrombocytopenia rapidly worsened with the appearance of peripheral basophilia three months later. He was diagnosed as having AML with basophilic differentiation transformed from MDS. At that time, monosomy 7 was detected by chromosomal analysis. We found that basophils can be confirmed on the basis of the positivity for CD203c and CD294 by flow cytometric analysis. We also found by cytogenetic analysis that basophils were derived from myeloblasts. He refused any chemotherapy and became transfusion-dependent. He died nine months after the transformation. We should keep in mind that MDS could transform to AML with basophilic differentiation when peripheral basophilia in addition to myeloblasts develops in patients with MDS.